PROTOTYPE ALAT PEMBATAS DAN PEMUTUS ARUS LISTRIK PASCABAYAR PADA RUMAH TANGGA BERBASIS SMARTPHONE - Rahma Farah Ningrum (Universitas Muhammadiyah Tangerang, 2018)
Electricity consumption in the household sector is 37.5% of total energy consumption. In 2017 Basic Electricity Fare (BEF) has increased 4 times. To suppress the high price that must be paid every month from the use of electrical energy and to anticipate the occurrence of energy crisis required a system that can limit the use of electrical energy. Therefore, a system that can control and limit the use of electrical energy. The system uses the arduino as the control center of the model circuit component, then connected to the current-breaker application on the user's smartphone. So with this system people can control and limit the usage of electric current with ease, therefore the savings on electrical energy can be done and also is one way to anticipate the occurrence of energy crisis in the future